The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7150/ijbs.7006
|View full text |Cite
|
Sign up to set email alerts
|

Subtype Identification in Acutely Dissociated Rat Nodose Ganglion Neurons Based on Morphologic Parameters

Abstract: Nodose ganglia are composed of A-, Ah- and C-type neurons. Despite their important roles in regulating visceral afferent function, including cardiovascular, pulmonary, and gastrointestinal homeostasis, information about subtype-specific expression, molecular identity, and function of individual ion transporting proteins is scarce. Although experiments utilizing the sliced ganglion preparation have provided valuable insights into the electrophysiological properties of nodose ganglion neuron subtypes, detailed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These major findings may explain, at least in part, that histamine could be a key player in gender-based differences in autonomic reflex function under physiological and disease conditions 5, 6. Consistent with our previous observation 34, a very low percentage of likely myelinated Ah-type neurons from male rats were verified using standard validation 32 and morphological parameters 33 in this investigation. However, male Ah-types do not follow the same pharmacological tendency 34 as female Ah-types regarding positive reactivity to αβ-methyl-adenosine triphosphate and negative reactivity to capsaicin.…”
Section: Discussionsupporting
confidence: 91%
“…These major findings may explain, at least in part, that histamine could be a key player in gender-based differences in autonomic reflex function under physiological and disease conditions 5, 6. Consistent with our previous observation 34, a very low percentage of likely myelinated Ah-type neurons from male rats were verified using standard validation 32 and morphological parameters 33 in this investigation. However, male Ah-types do not follow the same pharmacological tendency 34 as female Ah-types regarding positive reactivity to αβ-methyl-adenosine triphosphate and negative reactivity to capsaicin.…”
Section: Discussionsupporting
confidence: 91%
“…To answer this question, BRNs were isolated from adult female rats and individually identified electrophysiologically and fluorescently [9,10]. Our results showed that, in the presence of 1.0 μM 17β-E 2 , repetitive discharge evoked by step depolarization of Ah-type BRNs was significantly enhanced in a time-dependent fashion through all stimulus intensity applied ( Fig.…”
mentioning
confidence: 75%
“…To answer this question, the single-cell real time-polymerase chain reaction (RT-PCR) was performed on electrophysiologically 14 and morphologically 26 identified A-, Ah-, and C-type BRNs isolated from adult female rats. 23 As shown in Figure 2C and 2D, all neuronal subtypes expressed both AT 1 R and AT 2 R, whereas the averaged expression level of AT 1 R was ≈4× to 5× higher in A-type neurons than that in Ah-or C-type neurons, and AT 2 R expression level was ≈7-fold higher in Ah-type neurons compared with A-or C-type neurons.…”
Section: Afferent-specific Expression Of At 1 R and At 2 Rmentioning
confidence: 99%